Do patients with unexplained physical symptoms pressurise general practitioners for somatic treatment? A qualitative study. Issue 7447 (31st March 2004) - Ring, Adele; Dowrick, Christopher; Humphris, Gerry; Salmon, Peter
Abstract: Objectives To identify the ways in which patients with medically unexplained symptoms present their problems and needs to general practitioners and to identify the forms of presentation that might lead general practitioners to feel pressurised to deliver somatic interventions. Design Qualitative analysis of audiorecorded consultations between patients and general practitioners. Setting 7 general practices in Merseyside, England. Participants 36 patients selected consecutively from 21 general practices, in whom doctors considered that patients' symptoms were medically unexplained. Main outcome measures Inductive qualitative analysis of ways in which patients presented their symptoms to general practitioners. Results Although 34 patients received somatic interventions (27 received drug prescriptions, 12 underwent investigations, and four were referred), only 10 requested them. However, patients presented in other ways that had the potential to pressurise general practitioners, including: graphic and emotional language; complex patterns of symptoms that resisted explanation; description of emotional and social effects of symptoms; reference to other individuals as authority for the severity of symptoms; and biomedical explanations. Conclusions Most patients with unexplained symptoms received somatic interventions from their general practitioners but had not requested them. Though such patients apparently seek to engage the general practitioner by conveying the reality of their suffering, general practitioners respond symptomatically.